96.9k views
5 votes
Write the quadratic equation in general quadratic form below 3x^2 + 6x = 12

User Imikay
by
6.1k points

2 Answers

4 votes

Answer:

3x²+6x-12 = 0

Explanation:

We have given a quadratic equation.

3x²+ 6x = 12

We have to rewrite above equation in general quadratic equation.

The general form of quadratic equation is:

ax²+bx+c = 0 where a,b and c are constant.

Adding -12 to both sides of given equation, we have

3x²+6x+(-12) = 12+(-12)

3x²+6x-12 = 12-12

3x²+6x-12 = 0 is general form of quadratic equation where a = 3,b = 6 and c = -12.

User Tdgs
by
6.0k points
2 votes

Answer:
3x^(2)+6x-12=0

Explanation:

By definition a quadratic equation in general quadratic form is:


ax^(2)+bx+c=0

Therefore, to write the equation given in the problem above in in general quadratic form, you only need to subtract 12 from both sides of the equation.

Keeping this on mind, you obtain:


3x^(2)+6x-12=12-12\\3x^(2)+6x-12=0

User Saar Davidson
by
6.0k points